2019
DOI: 10.1177/1363461519851606
|View full text |Cite
|
Sign up to set email alerts
|

Mahi a Atua: A Māori approach to mental health

Abstract: Māori are the indigenous people of Aotearoa New Zealand. European colonisation had a devastating effect on their communities and their way of life. While there is some evidence of a renaissance of Māori culture in recent years, like other indigenous people across the world, they continue to be massively overrepresented in their country’s figures for poor mental and physical health. In this paper, we briefly review the literature on the Movement for Global Mental Health and review the case that has been made fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 31 publications
(27 reference statements)
0
7
0
Order By: Relevance
“…Recent qualitative research exploring effective and culturally appropriate care for Māori SMHAS users, particularly those with bipolar disorder, has shown the importance of incorporating te ao Māori, tikanga Māori (customs/ protocols), and involving whānau (family) in service delivery for Māori SMHAS users (Haitana et al, 2022a(Haitana et al, , 2022b(Haitana et al, , 2023Staps et al, 2019); approaches/elements which the 'medical model' has been described as incongruent with (Bush et al, 2019;Durie, 2011;Graham & Masters-Awatere, 2020;Haitana et al, 2022aHaitana et al, , 2022bStaps et al, 2019). Reports from some participants of an absence of Māori models of care in their workplace, suggests that increased utilization of Māori health models and clinical practice frameworks, such as Kaupapa Māori frameworks (Haitana et al, 2022a), Te Whare Tapa Whā (Durie, 1985), the Meihana model (Pitama et al, 2007), Te Ara Waiora a Tāne (Bush et al, 2019) and Mahi a Atua (Kopua et al, 2020), may be an important step in improving the quality of care for Māori SMHAS users. However, in order for the true benefits of this model/framework shift to be realized, there must also be adequate staff resourcing; previous research has indicated that high caseloads and short consultation times often lead clinicians to revert back to mainstream practices (Kopua, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Recent qualitative research exploring effective and culturally appropriate care for Māori SMHAS users, particularly those with bipolar disorder, has shown the importance of incorporating te ao Māori, tikanga Māori (customs/ protocols), and involving whānau (family) in service delivery for Māori SMHAS users (Haitana et al, 2022a(Haitana et al, , 2022b(Haitana et al, , 2023Staps et al, 2019); approaches/elements which the 'medical model' has been described as incongruent with (Bush et al, 2019;Durie, 2011;Graham & Masters-Awatere, 2020;Haitana et al, 2022aHaitana et al, , 2022bStaps et al, 2019). Reports from some participants of an absence of Māori models of care in their workplace, suggests that increased utilization of Māori health models and clinical practice frameworks, such as Kaupapa Māori frameworks (Haitana et al, 2022a), Te Whare Tapa Whā (Durie, 1985), the Meihana model (Pitama et al, 2007), Te Ara Waiora a Tāne (Bush et al, 2019) and Mahi a Atua (Kopua et al, 2020), may be an important step in improving the quality of care for Māori SMHAS users. However, in order for the true benefits of this model/framework shift to be realized, there must also be adequate staff resourcing; previous research has indicated that high caseloads and short consultation times often lead clinicians to revert back to mainstream practices (Kopua, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…This approach also addresses the discord between the dominant biomedical system and the beliefs and perspectives of Indigenous peoples, promoting engagement with services (Sylliboy and Hovey 2020), Liebenberg et al 2022). Re-engagement with Indigenous cultural and healing practices develops resilience and strength (Kopua et al 2020) and can contribute to supporting better outcomes.…”
Section: Characteristics Of Approaches and The Cultural Continuummentioning
confidence: 99%
“…Commentators often espouse 'universal claims' around successful positive education programmes based on Western assumptions, values, and contexts (Kern et al, 2020). The historical one-way flow of Western 'expertise' needs to shift to an environment that respects and values indigenous knowledge (Maree Kopua et al, 2020). In Aotearoa New Zealand, education policy and practice seeks to embrace indigenous perspectives on holistic wellbeing promotion: "Students' wellbeing is strongly influenced by ... where they come from, what they value and what they already know" (Ministry of Education, 2013, p. 17).…”
Section: Content | Contextmentioning
confidence: 99%